Use of Sato's curved laryngoscope and an insulated‐tip knife for endoscopic incisional therapy of esophageal web. Issue 4 (17th September 2014) - Ohtaka, Masahiko; Kobayashi, Shouji; Yoshida, Takashi; Yamaguchi, Tatsuya; Uetake, Tomoyosi; Sato, Tadashi; Hayashi, Akira; Kanai, Mari; Yamamoto, Takanori; Hatsushika, Kyosuke; Masuyama, Keisuke; Enomoto, Nobuyuki
<x xml:space="preserve">Abstract</x> We experienced two cases of esophageal web accompanying severe stricture that were treated by endoscopic incisions with an insulated‐tip knife (IT‐knife). With attention paid to the mucosa at the stricture, the lesion was incised with an IT‐knife without complications. Sato's curved laryngoscope was used even in cervical esophageal lesions and an excellent field was secured.